Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Kantor Perusahaan Umum Badan Urusan Logistik Kota Sampit Kabupaten Kotawaringin Timur - Masrukin Masrukin; Hermanto Hermanto (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Customer satisfaction is influenced by service quality factors, this study aims to find out and analyze how much influence the quality of service on customer satisfaction is felt by customers who use the service of Poor Rice (Raskin) at the Office of Public Companies Logistics Agency (Perum BULOG) in Sampit City Regency East Kotawaringin. The research method used in this study is the method of observation, questionnaire/questionnaire and documentation using a Likert scale and the method of determining the sample used is the error rate of 5% as many as 213 samples. Testing the hypothesis used is a statistical test with the formula